Fabrication of 3-D phononic crystals for thermal transport management - Savytskyi, Mykhailo (2016)
Thermal transport is an important physical phenomenon, and it has recently become even more relevant for the reduction of energy losses and the increase of efficiency in novel devices based on thermoelectricity [1]. Significant reduction of thermal conduction was recently achieved by coherent modification of phonon modes [2], with the help of periodic phononic crystal structures. However, currently the experimental studies have only been performed for two-dimensional (2-D) nanostructures. Theoretically, the magnitude of control of thermal transport should be even stronger in three-dimensional (3-D) phononic crystal structures. For that reason, the question arises how to fabricate the desired 3-D phononic crystal nanostructures and to measure its thermal conductivity.